Effects of the Uruguay Roundon Egypt and Morocco - Subramanian, Arvind (IMF Working Papers; Working Paper ;, 1996)
This paper presents simple computational techniques to examine a variety of effects of the Uruguay Round on developing country trade flows. These methods are applied to the cases of Egypt and Morocco to simulate the implications of the Round for their medium-term balance of payments. The analysis takes into account most-favored-nation tariff cuts, preference erosion, liberalization of trade in textiles and clothing, and potential increases in world food prices. The simulation results indicate that the overall balance of payments implications of the Uruguay Round for these countries, while negative, may not be very significant.